Clinical and immunological features of an APLAID patient caused by a novel mutation in PLCG2 - Peng, Qi; Luo, Dong; Yang, Yi; Zhu, Yinghua; Luo, Qingming; Chen, Huan; Chen, Dapeng; Zhou, Zhongjun; Lu, Xiaomei (Frontiers in Immunology, 2023)
Background: The APLAID syndrome is a rare primary immunodeficiency caused by gain-of-function mutations in the PLCG2 gene. We present a 7-year-old APLAID patient who has recurrent blistering skin lesions, skin infections in the perineum, a rectal perineal fistula, and inflammatory bowel disease. Methods: To determine the genetic cause of our patient, WES and bioinformatics analysis were performed. Flow cytometry was used for phenotyping immune cell populations in peripheral blood. Cytokines released into plasma were analyzed using protein chip technology. The PBMCs of patient and a healthy child were subjected to single-cell RNA-sequencing analysis. Results: The patient carried a novel de novo missense mutation c.2534T>C in exon 24 of the PLCG2 gene that causes a leucine to serine amino acid substitution (p.Leu845Ser). Bioinformatics analysis revealed that this mutation had a negative impact on the structure of the PLCγ2 protein, which is highly conserved in many other species. Immunophenotyping by flow cytometry revealed that in addition to the typical decrease in circulating memory B cells, the levels of myeloid dendritic cells (mDCs) in the children's peripheral blood were significantly lower, as were the CD4+ effector T cells induced by their activation. Single-cell sequencing revealed that the proportion of different types of cells in the peripheral blood of the APLAID patient changed. Conclusions: We present the first case of APLAID with severely reduced myeloid dendritic cells carrying a novel PLCG2 mutation, and conducted a comprehensive analysis of immunological features in the ALPAID patient, which has not been mentioned in previous reports. This study expands the spectrum of APLAID associated immunophenotype and genotype. The detailed immune analyses in this patient may provide a basis for the development of targeted therapies for this severe autoinflammatory disease.